The Influence of Leadership Style and Communication Patterns on Work Motivation of Supervisors in the Education Office of Sukabumi Regency - Lukitasari, Tari; Susanti, Aty; Amperawati, Susani; Miswan, Miswan (Indonesian Journal of Social Science Research, 2025)
This study aims to investigate and analyze the influence of leadership style and communication patterns on the work motivation of supervisors in the Education Office of Sukabumi Regency. Employing a quantitative approach, the research utilized a questionnaire as a data collection tool. The population for this study consisted of all supervisors within the Education Office of Sukabumi Regency, totaling 70 individuals, all of whom were included in the sample using a saturated sampling technique. The data analysis method employed was multiple regression analysis. Based on descriptive statistical analysis, it was found that the work motivation of supervisors was categorized as high, leadership style was categorized as low, and communication patterns were categorized as high. The hypothesis testing results indicated that: (1) Leadership style has a positive and significant effect on the work motivation of supervisors; (2) Communication patterns have a positive and significant effect on the work motivation of supervisors; and (3) Leadership style and communication patterns together have a positive and significant effect on the work motivation of supervisors, accounting for 65.5% of the influence, while 34.5% is affected by other variables or factors not included in this study.